Neuropsychological predictors of response to cognitive behavioral therapy for posttraumatic stress disorder in persons with severe mental illness. (January 2018) - Mueser, Kim T.; McGurk, Susan R.; Xie, Haiyi; Bolton, Elisa E.; Jankowski, M. Kay; Lu, Weili; Rosenberg, Stanley D.; Wolfe, Rosemarie
Abstract: This study examined whether cognitive functioning was related to treatment outcomes in persons with severe mental illness who received a cognitive behavioral therapy (CBT) program for co-occurring posttraumatic stress disorder (PTSD). The study sample was drawn from a larger controlled trial of 108 persons with severe mental illness and PTSD comparing the effects of CBT with treatment as usual on PTSD and related outcomes, with assessments conducted at baseline, post-treatment, and 3- and 6-month follow-ups. Among the 54 persons in CBT, 49 were administered a neuropsychological battery at baseline and 40 were exposed to the CBT program. Statistical analyses of these 40 participants were conducted to evaluate whether cognitive functioning was related to participation in the CBT program, completion of homework assignments, and improvements in PTSD, and other outcomes. Cognitive functioning was not related to participation in CBT or completion of homework. Lower cognitive functioning predicted less learning of information about PTSD at post-treatment and follow-up, but not less clinical benefit from CBT in PTSD diagnosis or symptoms, other symptoms, or health. The results suggest that cognitive impairment does not attenuate response to the CBT for PTSD program in persons with severe mental illness. Clinical Trials.gov Identifier: NCT00053690 Highlights: CBT is effective at treating PTSD in people with severe mental illness (SMI). It is unknown whether cognitive impairment limits response to CBT for PTSD in persons with SMI. A cognitive battery was given to participants with SMI in a CBT program to evaluate whether it predicted clinical outcomes. Lower cognitive functioning predicted less learning about PTSD, but was not related to other outcomes in the CBT program. Cognitive impairment does not appear to limit clinical benefit from CBT for PTSD in people with SMI.